2021
DOI: 10.1088/1755-1315/788/1/012226
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the Covid-19 pandemic on broiler farms in Moncongloe District, Maros Regency South Sulawesi

Abstract: The Covid-19 pandemic has an impact on all sectors of the economy including broiler farming. The purpose of this study was to determine the impact of the Covid-19 pandemic on broiler chicken farming in Moncongloe District, Maros Regency. This research was conducted in August - September 2020. The data collection method used literature review, observation and interviews. The broiler chicken farm industry and business owners are feeling the positive and negative impacts of the Covid-19 pandemic. The positive imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Recent data showed that there was a decrease in chicken demand from 2019 to 2020 (509385–498367 chickens), as evidenced by the reduced number of chickens sold in 2020 [ 12 ]. This decreased demand is consistent with the broader trends observed during pandemic, where various factors such as lockdowns, reduced consumer spending, and supply chain disruptions have reshaped consumption patterns [ 10 ].…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…Recent data showed that there was a decrease in chicken demand from 2019 to 2020 (509385–498367 chickens), as evidenced by the reduced number of chickens sold in 2020 [ 12 ]. This decreased demand is consistent with the broader trends observed during pandemic, where various factors such as lockdowns, reduced consumer spending, and supply chain disruptions have reshaped consumption patterns [ 10 ].…”
Section: Introductionsupporting
confidence: 80%
“…One of the most significant challenges in the poultry supply chain has been the catastrophic impact of COVID-19 [ 6 ]. This pandemic has led to disruptions in production levels, shifts in customer demand and product access, as well as economic challenges for broiler breeders and traders [ [7] , [8] , [9] , [10] , [11] ]. The reduced demand for broiler chickens will certainly disrupt the production process starting from DOC, production and marketing processes, where the broiler industry is a living thing industry that has perishable properties.…”
Section: Introductionmentioning
confidence: 99%